2018
DOI: 10.1021/acs.chemmater.8b00960
|View full text |Cite
|
Sign up to set email alerts
|

Design of Near-Infrared-Absorbing Unsymmetrical Polymethine Dyes with Large Quadratic Hyperpolarizabilities

Abstract: Fifteen heptamethine dyes in which a tricyanofuran acceptor is linked to donors of different strength were synthesized, and their absorption, thermal, electrochemical, and second-order nonlinear optical properties were investigated. While the variation of the peripheral bulky substituents allowed a decrease of the intermolecular interactions in the solid state, subtle engineering of the heterocyclic donor provided dyes with electronic structures that varied between dipolar and cyanine-like (i.e. with little bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…[11,12] Some polymethines have also been extensively studied for nonlinear optical applications, such as alloptical signal processing or optical limiting, in the telecommunication wavelengths range [1.3-1.5 μm]. [13][14][15][16][17][18][19] The development of such applications requires the optimization of the optical properties of the material through a precise molecular-level manipulation of the electronic structure of the polymethine dyes, by controlling the nature of the counterion. [16,[20][21][22] In fact, it is well known that polymethines can present other ground state electronic structures, as the charge is localized at one extremity, breaking the symmetry of the conjugated backbone and forming a dipolar chromophore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] Some polymethines have also been extensively studied for nonlinear optical applications, such as alloptical signal processing or optical limiting, in the telecommunication wavelengths range [1.3-1.5 μm]. [13][14][15][16][17][18][19] The development of such applications requires the optimization of the optical properties of the material through a precise molecular-level manipulation of the electronic structure of the polymethine dyes, by controlling the nature of the counterion. [16,[20][21][22] In fact, it is well known that polymethines can present other ground state electronic structures, as the charge is localized at one extremity, breaking the symmetry of the conjugated backbone and forming a dipolar chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…[23] This electronic state, also known as polyene-like state, features a broad absorption band (form II, Figure 1). This phenomenon, generally referred to as "crossing the cyanine limit" in the literature, can be achieved by (i) the lengthening of the conjugated skeleton, [24][25][26] (ii) the modification of the donor end group, [19,27] (iii) of solvent polarity [28] or (iv) monitoring ion-pairing effects. [10,29] Furthermore, the existence of a third ground state electronic structure called bis-dipole has also been described as the charge is localized on the central Csp 2 atom of the bridge under the influence of vicinal electron-donating moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Pascal et al obtained the push-pull dyes 33-34 with tricyanofuran acceptor linked to donors of various strengths, by two consecutive condensations, and investigated their second-order nonlinear optical properties [109]. It was found that a high intrinsic hyperpolarizability coupled with a high static dipolar moment results in excellent μβ values for polymethine dyes containing pyran, thiopyran, selenopyran, and benzoindoline moieties, and therefore, these dyes are promising for electro-optical modulation.…”
Section: Synthesis Of the Nonlinear Optical Dyesmentioning
confidence: 99%
“…Indeed, absorption spectrum of D-π-A structures (where D and A respectively stand for donor and acceptor and π corresponds to the polyenic spacer) can be easily tuned by modifying the electron-donating ability of the donor or the electron-re leasing ability of the acceptor. Parallel to this, elongation of the polyenic spacer enables both to redshift the absorption spectrum of the dyes by destabilizing the highest occupied molecular orbital (HOMO) without significantly affecting the position of the lowest unoccupied molecular orbital (LUMO) [121][122][123][124].…”
Section: Introductionmentioning
confidence: 99%